Antioxidant and antibacterial activity of different solvent extracts of leaves and stem of Alyxia reinwardtii Blume - Sitthan, Vanishri Kaly; Abdallah, Muhamad Salihu; Nallappan, Meenakshii; Choi, Sang-Ho; Paik, Jin-Hyub; Go, Rusea (Persatuan Biologi Gunaan Malaysia, 2023)
Alyxia reinwardtii Blume (Pulasari) Apocynaceae is being widely used as a traditional medicine in treating various illnesses due to its phenolic, coumarins, lignans, iridoid glycosides alkaloids and flavonoids content. These compounds in A. reinwardtii were reported to be useful as medicinal and agricultural potentials. Hence, A. reinwardtii meets the rationale for antioxidant and antibacterial studies to replace synthetic substances using different solvents on the leaves and stem of A. reinwardtii using cold maceration. The Folin-Ciocalteu reagent assay was used to estimate the phenolic content of extracts. The total flavonoid content was determined using aluminum chloride. The antioxidant capacity of the samples was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical and Ferric Reducing Antioxidant Power (FRAP) assay. Disc Diffusion Assay (DDA), Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) were conducted to evaluate the antibacterial activity of Escherichia coli and Bacillus cereus growth. Methanol was determined as the most effective solvent due to the highest crude yield obtained, (19.47 ± 2.80 %). Acetone showed the highest TPC content (170.44 ± 10.99 mg GAE/g) while hexane showed the highest TFC content (2957 ± 91.24 mg QE/g). Moreover, for DPPH, methanol inhibited the highest antioxidant (75.81 ± 12.62 %) and hexane for FRAP assay (2278.89 ± 69.47 mg AAE/g). Hexane extract is potentially effective with variable efficiency with DDA (11.17 ± 4.48 mm) while methanol extracts with MIC (0.63 μg/mL) and MBC (2.50 μg/mL) against E. coli. The results indicated that methanolic and hexane extract using cold maceration showed optimum antioxidant and antibacterial activity. The present study advocates that A. reinwardtii was a source of substantial antioxidant and antibacterial agents for potential pharmaceutical applications.